Serbia and Montenegro : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents the Joint Staff Assessment of Serbia and Montenegro's Poverty Reduction Strategy Paper (PRSP). The PRSP for Serbia and Montenegro comprises a union-level overview and a PRSP for each of the two republics. The Montenegrin PRSP is broadly in line with the Agenda of Economic Reforms, the key government document setting priorities. The Serbian PRSP is also broadly consistent with other government strategies and plans, including 'Serbia on the Move,' a document presented at a donor coordination meeting in November 2003.